Slovene Emigration Material: A Round Table, Ljubljana, 31 May 2000 - Drnovšek, Marjan (Two Homelands, 2000)
On 31 May 2000 a round table on the theme ‘Slovene Emigration Material’ was held in the Little Hall of SAZU’s Scientific Research Center in Ljubljana. Discussion was limited to issues relating to material created by emigrants and brought by various routes to Slovenia or the Slovene areas of Italy and A ustria (material from archivesand museums, ethnological material, art, literature, film and material recorded in otherways). To coincide with the round table a Guide to the Archive Material of the ZRC SAZU Institute for Slovene Emigration Studies was published. The Guide was preparedby Dean Ceglar. It was also intended as an encouragement and a model publication to help other holders of this type of material.